Is Financial Education Positively Associated with Consumer Stock Market Satisfaction? Evidence from China - Fuzhong Chen; Ji Zhang; Jing Jian Xiao; Jinwei Chen (Discrete Dynamics in Nature and Society)
This study aims to investigate the associations between financial education and consumer stock market satisfaction. Consumer financial education is measured through the objective aspect incorporating formal and informal financial knowledge education, and the subjective aspect is reflected through consumers’ attitudes toward financial education. Using data from China’s urban consumers, the results indicate a positive association between financial education and consumer stock market satisfaction. The findings suggest that consumers who were financially literate at high schools or colleges are more satisfied in participating in the stock market. Moreover, consumers who spend more money and time, as well as those who think financial education is more important, feel more satisfied in participating in stock market investment activities. The results imply that it is necessary to increase the supply of formal financial education in high schools and universities, encourage consumers to invest more in the informal education of financial knowledge, and promote policymakers to formulate informative policies to make consumers aware of the importance of financial education.